THE RECEPTION OF GONCOURT BROTHERS' CREATIVE WORK IN THE FRENCH CRITISISM - Яцків, Н. Я. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The evolution of Goncourt brothers' reception in the French literature is researched in the article. Chronological principle has allowed to single out three periods. The first one began at the end of the XIX century in the context of naturalism. At the beginning of the XX century researches tried to define the writers' innovation in theme-based and problem matters. Complex study of stylistic range of expression began in the middle of the century.